2020
DOI: 10.17743/jaes.2020.0038
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Evaluation of Mitigation Approaches of Impairments due to Spatial Undersampling in Binaural Rendering of Spherical Microphone Array Data

Abstract: Spherical microphone arrays (SMAs) are widely used to capture spatial sound fields that can then be rendered in various ways as a virtual acoustic environment (VAE) including headphone-based binaural synthesis. Several practical limitations have a significant impact on the fidelity of the rendered VAE. The finite number of microphones of SMAs leads to spatial undersampling of the captured sound field, which, on the one hand, induces spatial aliasing artifacts and, on the other hand, limits the order of the sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Although the linear-phase component at high frequencies may be less important for lateral localization [26], [27], its removal still introduces errors in the binaural signal, and may affect other perceptual attributes [28], [29]. In [30], Lübeck et al showed that the MagLS method achieved similar perceptual improvement to the equalization methods for binaural reproduction with order 3 and above. In summary, despite of the significant advance in this field, current methods for binaural reproduction that are based on low-order HRTF and sound-field representations seem to degrade perception compared to a high-order reference.…”
Section: Introductionmentioning
confidence: 99%
“…Although the linear-phase component at high frequencies may be less important for lateral localization [26], [27], its removal still introduces errors in the binaural signal, and may affect other perceptual attributes [28], [29]. In [30], Lübeck et al showed that the MagLS method achieved similar perceptual improvement to the equalization methods for binaural reproduction with order 3 and above. In summary, despite of the significant advance in this field, current methods for binaural reproduction that are based on low-order HRTF and sound-field representations seem to degrade perception compared to a high-order reference.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of the scattering removal, the available data suggest that the presented approach produces a lower error for horizontally propagating sound fields compared to the cylindrical array from [14], which was composed of multiple circular rings of microphones with total number of microphones that was equal to a conventional spherical array of the same SH order. The circumstance that typical arrays are generally not capable of capturing the sound field accurately at high frequencies has been shown to be tolerable particularly when binaural rendering is the targeted application [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 5 shows the NMSE according to (22) for several filter designs with different levels of regularization, obtained by varying the modeled microphone signal SNR (given by 1/σ 2 v ). The general trend is that the MSE increases towards high frequencies where microphone array spatial aliasing, increasingly complex HRTF beam patterns, and a limited number of microphone channels prevent accurate synthesis of the target beam pattern.…”
Section: B Filter Designmentioning
confidence: 99%
“…Approaches have been developed to mitigate the effects of limited SH-order on binaural rendering [22]. One approach mentioned in [22] is pre-processing of the HRTF target responses, which can reduce the SH-order needed to represent the HRTFs without giving perceptual consequences [23] [24] (this idea could also be applied to our case of direct binaural signal estimation and is a possibility for future research).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation